أسطرة الواقع في شعر وليد سيف: حكاية خضرة وزيد الياسين نموذجاً - الديك، إحسان يعقوب (جامعة النجاح الوطنية, 2008)
يحاول البحث القاء الضوء على منهج التفكير الأسطوري الذي لازم الانسان في كل مراحل حياته، ويتخذ من شعر وليد سيف ذي الطاقات الدرامية والرؤى الحلمية، والثقافة الشعبية، والدوال التأويلية ميدانا، ومن حكاية خضرة وزيد الياسين نموذجاً. فيبرز دوافع الأسطرة عند هذا الشاعر وعناصرها وطرائقها، ويكشف عن ماهية هاتين الشخصيتين اللتين تحولتا إلى رمزين أسطوريين، أو نموذجيين أصيلين، جدلتا علاقة الشهيد بأمه الأرض، وأدخلتا التجربة الفلسطينية في أتون أساطير الموت والانبعاث؛ فخضرة/ الأرض تجذب الفارس الشهيد/ زيد الياسين بخيط سحري إلى رحمها، ليخصبها، ويبعث بذرة الحياة في أحشائها، ليموت ويموت، وفي كل موت يبعث حيا، ويتحول إلى أسطورة تكوين وميلاد فرح، إذ الموت عنده وقت بين الرماد والورد ليس إلا. This research sheds light on the mythological thinking throughout history poem that has accompanied the human being during all his life stages. The study focuses on Walid Saif s poem, which is renowned for its drama energy, dream vision, popular culture, and articulation as a data base, and takes Ghadra and Zaid story as a model. This research endeavors to unveil the motives of depicting reality in a story in this poet’s work, in addition to its elements and means. More specifically, it tries to uncover the real nature of the two characters, which became myth symbols, or authentic models that tied the relationship between the martyr and the motherland. Such characters hooked the Palestinian experience with the tales of death and resurrection. Ghadra (green) is the land that towed the Knight Zaid Al- Yasin with a magic thread to its womb to impregnate her and revive life in her viscera. Later, he would die and die again, and after each death, he would come alive again. Then, he would become a story of recreation and birth of happiness. Death here is merely a time between the ash and the roses.
Keywords: الأسطورة في الشعر العربي -- الشعر العربي -- الشعراء العرب -- سيف ، وليد -- الدواوين والقصائد -- النقد الأدبي -- فلسطين -- التراث الشعبي -- العصر الحديث